PEMBERDAYAAN PEREMPUAN MELALUI PEMANFAATAN PEKARANGAN MENGGUNAKAN LIMBAH DAPUR SEBAGAI PUPUK ORGANIK DI JEMAAT RANTE TAGARI KLASIS TALLUNGLIPU - Driyunitha Driyunitha; Yulius Pakiding; Sion Oktafianus; Ernytha A Galla (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
Household organic waste remains an environmental challenge that has not been optimally managed by many communities. At the same time, home yards possess significant potential to support household food security when utilized productively. This community service program aimed to enhance community knowledge and skills in processing kitchen waste into liquid organic fertilizer and optimizing home yard utilization for vegetable cultivation. The target participants were 302 members of the Women's Fellowship of Toraja Church (Persekutuan Wanita Gereja Toraja/PWGT) at Rante Tagari Congregation, Tallunglipu Classis. This group was selected because of its strategic role in household management, including food preparation, kitchen waste management, and home yard utilization. The program was conducted over a three-month period through observation, socialization, training, demonstration, mentoring, and evaluation activities. The results indicated an improvement in participants' knowledge and skills in producing liquid organic fertilizer from household kitchen waste. Participants were able to independently produce and apply organic fertilizer to vegetables cultivated in their home yards. During the mentoring period, various vegetables, including mustard greens, spinach, kale, tomatoes, eggplants, and chili peppers, showed good growth and were utilized for household consumption. In addition to improving yard productivity, the program encouraged positive behavioral changes in household waste management, reduced dependence on inorganic fertilizers, and increased environmental awareness. The findings demonstrate that women's empowerment through the utilization of kitchen waste and home yards can contribute to household food security while promoting a cleaner, greener, and more sustainable environment.